The Prohibition of Racism in the Qur'an - Salwa Nabila Nur Habibah; Yumna Yumna (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the prohibition of racism in the Qur'an regarding human equality. The method used is a qualitative method through literature study by applying content analysis. The results and discussion of this research include general views of racism, interpretation of verses of the Qur'an related to racism and human equality, and the prohibition of the Qur'an on racism. The conclusion of the study is that the Qur'an applies the concept of human equality while at the same time rejecting acts of racism, as well as offering solutions and prevention against it. This study recommends conducting research with other scientific methods that are interdisciplinary, or may not be transdisciplinary.